Social Media Marketing Influence on Purchase Intention via Brand Image and Trust - Ryan Cahya Anindito; Anas Hidayat (International Journal of Multidisciplinary Research of Higher Education, 2026)
The rapid expansion of social media has transformed how e-commerce platforms engage with consumers. However, empirical evidence regarding the mediating roles of brand image and brand trust in explaining the effect of social media marketing on purchase intention remains limited and inconsistent. This study examines the influence of social media marketing on purchase intention in Shopee by incorporating brand image and brand trust as mediating variables. This research adopts a quantitative approach using a survey method. Data were collected from 300 active Shopee users in Yogyakarta who had been exposed to Shopee social media content. The sample was selected using a non-probability sampling technique with a convenience sampling approach. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that social media marketing influences brand image and brand trust, which subsequently affect purchase intention. Both brand image and brand trust function as mediators in the relationship between social media marketing and purchase intention. These results confirm the Stimulus-Organism-Response (SOR) framework, where social media marketing acts as the stimulus, brand image and brand trust represent the organism, and purchase intention represents the response. This study contributes to the literature by strengthening the application of the SOR model in digital marketing and highlighting the role of psychological mechanisms in consumer behavior. The results suggest that e-commerce platforms should design social media content that is engaging, credible, informative, and aligned with current trends to strengthen consumer perception and trust, thereby enhancing purchase intention.